MODEL PERENCANAAN PARTISIPATIF PEMBANGUNAN DI KECAMATAN BOJONG KABUPATEN PURWAKARTA - Wanwan Jamaludin (Sekolah Tinggi Teknologi Wastukancana, 2019)
Abstract. The main problem in this research is that there are complaints from the community related to the fact that the proposed activities or programs (problem formulation) from the sub-district receive intervention in the interests and power of decision makers at the regional legislative and OPD levels, which in turn causes the accountability of the process and results of planning to be questioned. Public The research refers to Alexander Abe's opinion, explaining that participatory planning measures include investigation, problem formulation, identification of carrying capacity, formulation of goals, determining detailed steps and knowing and analyzing participatory development planning models. This research uses descriptive qualitative method. The data collection process was carried out by means of observation, in-depth interviews, and documentation study. The result of this research is that the participatory planning process is only at the stage of investigation and problem formulation that has involved the community of the Bojong sub-district, while the carrying capacity identification stage, determining detailed steps is not included. In the participatory planning model it is only limited to proposed activities. Therefore it is necessary to involve all stakeholder elements in the District of Bojong in participatory planning starting from the investigation stage, problem formulation, identification of carrying capacity, formulation of objectives, determining detailed steps. The result of participatory planning is in the form of program or activity planning. This study aims to describe the participatory planning process of development in Bojong District, Purwakarta Regency Keywords: participatory planning, and participatory planning model design